Patient Perception of Mammographic Breast Density Notification Laws [37K]. (May 2017) - Metcalfe-Klaw, Robin; Woodman, Sarah; Fenimore, Emily; Copit, Debra; Jaspan, David; Goldberg, Jay
Abstract : INTRODUCTION: 50% of women undergoing screening mammography will be diagnosed with increased breast density. These women may have slightly increased risk for and decreased detection of breast cancer (RR 1.2 – 2.1). Many states have passed laws requiring patient notification of increased breast density and offering additional breast imaging. Few states, however, require insurance coverage of additional imaging. METHODS: After IRB approval, a survey study of asymptomatic women undergoing screening mammography was performed. Data collected included patient demographics and patient knowledge of and perception towards breast density notification laws. Patients were additionally queried regarding if they would undergo additional breast imaging if notified of increased breast density on mammography. Statistical analysis was performed using Chi-squared, Fisher's exact test, and Student's t-test. RESULTS: 18% of women were aware of breast density notification laws. 40% of women reported they would be worried if notified of increased breast density. 84% of women would choose to undergo additional breast imaging if the cost was completely covered by insurance compared to only 44% paying out of pocket.98% of women believed insurance coverage for additional imaging should be required. 88% believed breast density notification laws were economically discriminatory. CONCLUSION: If notified of increased breast density on their mammogram, women are twice as likely to undergo additional breast imaging when fully covered by insurance. However, approximately only half of these women would be willing to pay for additional breast imaging out of pocket. Breast density notification laws are economically discriminatory as they require offering additional breast imaging without mandating insurance coverage.